PENGARUH PENGGUNAAN MEDIA MINIATUR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS V MIN 3 POLMAN KEC. TAPANGO KAB. POLEWALI MANDAR - Asriani Asriani; Umar Sulaiman; Rosdiana Rosdiana (Universitas Islam Negeri Alauddin Makassar, 2022)
This study discusses the effect of using miniature media on the learning outcomes of fifth gradestudents at MIN 3 Polman Kec. Tapango Kab. Polewali Mandar, The purpose of this study wasto determine 1) the learning outcomes of students in science subjects for class V MIN 3 PolmanKec. Tapango Kab. Polewali Mandar without the use of miniature media 2) student learningoutcomes in science subjects for class V MIN 3 Polman Kec. Tapango Kab. Polewali Mandar withthe use of miniature media 3) The effect of using miniature media on student learning outcomes inscience subjects for class V MIN 3 Polman Kec. Tapango Kab. Polewali Mandar. This researchuses a quantitative research type of pre-experimental design and one-group pretest-posttest researchdesign. The population in this study were all students of class V MIN 3 Polman Kec. TapangoKab. Polewali Mandar, totaling 18 students. The sampling technique used is the saturated sampletechnique. The instruments used in this study were learning outcomes tests and documentation.Data analysis techniques used inferesnial statistics and descriptive statistics. Based on dataanalysis using descriptive statistics, the average value of students before the use of miniature mediawas 50.28 and the average after using miniature media was 79.44. The results of inferentialstatistical analysis obtained tcount 29.180 while for ttable value of 1.739 which means that tcount> ttable is 29.180 > 1.739. This shows that HO is rejected and H1 is accepted. When viewed fromthe significant value H1 is accepted if it is significant < α that is 0.000 <0.05. Thus, it can beconcluded that learning with the use of miniature media shows that there is an effect of usingminiature media on students' science learning outcomes.